2004
DOI: 10.1016/j.eupc.2004.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in atrial refractoriness following DC cardioversion of persistent atrial fibrillation in man

Abstract: Prolongation of the atrial ERP occurred following restoration of SR in persistent AF patients but was not maintained and displayed a biphasic pattern such that by 2 weeks the ERP had returned to baseline values. Despite this finding, a longer ERP at 24 h post cardioversion was associated with maintenance of SR in the medium-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recovery has also been demonstrated in human atria 3,[23][24][25][26] . On the other hand, a remarkable vulnerability to recurrence during post-cardioversion period has been observed while reverse remodeling is yet incomplete 23 .…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Recovery has also been demonstrated in human atria 3,[23][24][25][26] . On the other hand, a remarkable vulnerability to recurrence during post-cardioversion period has been observed while reverse remodeling is yet incomplete 23 .…”
Section: Introductionmentioning
confidence: 77%
“…Most studies about electrical atrial remodeling in humans have assessed subjects with and without overt cardiovascular disease [23][24][25]27 . Although micro structural atrial changes have been observed in lone AF 29 , gross and ultra-structural anatomic changes due to underlying cardiac disease, such as fibrosis, may persist indefinitely, despite the restoration to sinus rhythm and may be responsible for persistent electrophysiological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations